SISTEM SENSOR NIRKABEL UNTUK MONITORING EFISIENSI PANEL SURYA - Pakradiga, Ahlan; Suryono, Suryono (BERKALA FISIKA, 2019)
Solar panels are devices consist of several solar cells that convert light into electrical energy. In order to work optimally, a monitoring system to electrical current, voltage, and light intensity in solar cells is needed. The monitoring system can be wirelessly carried out, so that solar panels can be remotely monitored without having to go to the field. The solar panel monitoring system used a wireless sensor system that uses sensors, System on Chip (SoC) WiFi Microcontroller, and computers. The sensors used were ACS712 current sensor, voltage sensor, and BH1750 light intensity sensor module. Before it was used, the current sensor and voltage sensor should be characterized and calibrated. Data stored in the database can be processed to calculate savings on solar panels in real time using php programming, then it was transferred to the web. The characterization equation for the current sensor is y = 944.9x + 13597.0, the average error for calibrating the current sensor is 3.39%. The characterization equation for the voltage sensor is y = 471.2x – 206.2 and the average error for the voltage sensor calibration is 0.77%. Sensor calibration is obtained by an average error of 1.10%. The efficiency of solar panels at bright times is 12.49%. In this study, it has been found that the efficiency of solar panels is influenced by the intensity of sunlight.Keywords: solar panel, monitoring system, remotely, sensor, efficiency of solar panels